Tanfidz An-Nazhariyah As-Sulukiyah fi Ta’lim Al-Mufradat lit-Thullab Al-Judud bi Ma’had Dar-As-Salam Gontor Al-Haram Al-Awal - Sa'idah, Mandrasi Amira; Arifin, Muhammad Syamsul; Habibirrahman, Muhammad (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2022)
Darussalam Gontor Islamic Institution Campus 1 is an educational institution which prefer on Arabic and English in its curriculum. Actually, Arabic for most of new students has become a new difficult language because only a few of them have learned. Due to solving this circumstance, Arabic teaching learning especially vocabularies must be conducted intensively in the beginning of their studies. Behaviourism theory as one of the psychological theories stated that every human receives types of responses from their environment and always communicate each other by their own languages. Therefore, this theory is a compatible in vocabulary teaching learning that requires stimulus, response, reinforcement and language environment. This study purposed to explore behaviourism in conducting vocabularies teaching learning for new students in Darussalam Gontor Islamic Institution. The study is a field researching as kind of descriptive qualitative study. For data collecting, it used observation, interview and written documents. For analysing data, it used interactive method. The study resulted that behaviourism in conducting vocabularies teaching learning for new students were represented in three aspects: 1) positive stimulus from teacher; 2) positive response from students and 3) positive reinforcement from both teacher-student. Ù…Ø¹Ù‡Ø¯ Ø¯Ø§Ø± Ø§Ù„Ø³Ù„Ø§Ù… ÙƒÙˆÙ†ØªÙˆØ± Ø§Ù„ØØ±Ù… Ø§Ù„Ø£ÙˆÙ„ Ù‡ÙŠ Ù…Ø¤Ø³Ø³Ø© ØªØ¹Ù„ÙŠÙ…ÙŠØ© ØªÙØ¶Ù„ Ø§Ù„Ù„ØºØªÙŠÙ† Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆØ§Ù„Ø¥Ù†Ø¬Ù„ÙŠØ²ÙŠØ© ÙÙŠ Ù…Ù†Ø§Ù‡Ø¬Ù‡Ø§. ÙÙŠ Ø§Ù„ÙˆØ§Ù‚Ø¹ ØŒ Ø£ØµØ¨ØØª Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ø§Ù„Ù†Ø³Ø¨Ø© Ù„Ù…Ø¹Ø¸Ù… Ø§Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ø¬Ø¯Ø¯ Ù„ØºØ© Ø¬Ø¯ÙŠØ¯Ø© ØµØ¹Ø¨Ø© Ù„Ø£Ù† Ø§Ù„Ù‚Ù„ÙŠÙ„ Ù…Ù†Ù‡Ù… ÙÙ‚Ø· Ù‚Ø¯ ØªØ¹Ù„Ù…Ù‡Ø§. Ø¨Ø³Ø¨Ø¨ ØÙ„ Ù‡Ø°Ø§ Ø§Ù„Ø¸Ø±Ù ØŒ ÙŠØ¬Ø¨ Ø¥Ø¬Ø±Ø§Ø¡ ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø®Ø§ØµØ© Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ø¨Ø´ÙƒÙ„ Ù…ÙƒØ«Ù ÙÙŠ Ø¨Ø¯Ø§ÙŠØ© Ø¯Ø±Ø§Ø³ØªÙ‡Ù…. Ø°ÙƒØ±Øª Ù†Ø¸Ø±ÙŠØ© Ø§Ù„Ø³Ù„ÙˆÙƒÙŠØ© ÙƒÙˆØ§ØØ¯Ø© Ù…Ù† Ø§Ù„Ù†Ø¸Ø±ÙŠØ§Øª Ø§Ù„Ù†ÙØ³ÙŠØ© Ø£Ù† ÙƒÙ„ Ø¥Ù†Ø³Ø§Ù† ÙŠØªÙ„Ù‚Ù‰ Ø£Ù†ÙˆØ§Ø¹Ù‹Ø§ Ù…Ù† Ø§Ù„Ø§Ø³ØªØ¬Ø§Ø¨Ø§Øª Ù…Ù† Ø¨ÙŠØ¦ØªÙ‡ ÙˆÙŠØªÙˆØ§ØµÙ„ Ø¯Ø§Ø¦Ù…Ù‹Ø§ Ù…Ø¹ Ø¨Ø¹Ø¶Ù‡Ù… Ø§Ù„Ø¨Ø¹Ø¶ Ø¨Ù„ØºØ§ØªÙ‡Ù… Ø§Ù„Ø®Ø§ØµØ©. Ù„Ø°Ù„Ùƒ ØŒ ÙØ¥Ù† Ù‡Ø°Ù‡ Ø§Ù„Ù†Ø¸Ø±ÙŠØ© Ù…ØªÙˆØ§ÙÙ‚Ø© ÙÙŠ ØªØ¹Ù„Ù… Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ø§Ù„ØªÙŠ ØªØªØ·Ù„Ø¨ Ø§Ù„ØªØÙÙŠØ² ÙˆØ§Ù„Ø§Ø³ØªØ¬Ø§Ø¨Ø© ÙˆØ§Ù„ØªØ¹Ø²ÙŠØ² ÙˆØ§Ù„Ø¨ÙŠØ¦Ø© Ø§Ù„Ù„ØºÙˆÙŠØ©. ØªÙ‡Ø¯Ù Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¥Ù„Ù‰ Ø§Ø³ØªÙƒØ´Ø§Ù Ø§Ù„Ø³Ù„ÙˆÙƒÙŠØ§Øª ÙÙŠ Ø¥Ø¬Ø±Ø§Ø¡ Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ø§Ù„ØªÙŠ ØªØ¯Ø±Ø³ Ø§Ù„ØªØ¹Ù„Ù… Ù„Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ø¬Ø¯Ø¯ ÙÙŠ Ù…Ø¹Ù‡Ø¯ Ø¯Ø§Ø± Ø§Ù„Ø³Ù„Ø§Ù… ÙƒÙˆÙ†ØªÙˆØ±. Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¹Ø¨Ø§Ø±Ø© Ø¹Ù† Ø¨ØØ« Ù…ÙŠØ¯Ø§Ù†ÙŠ ÙƒÙ†ÙˆØ¹ Ù…Ù† Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø§Ù„ÙˆØµÙÙŠØ© Ø§Ù„Ù†ÙˆØ¹ÙŠØ©. Ù„Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ØŒ Ø§Ø³ØªØ®Ø¯Ù…Øª Ø§Ù„Ù…Ù„Ø§ØØ¸Ø© ÙˆØ§Ù„Ù…Ù‚Ø§Ø¨Ù„Ø© ÙˆØ§Ù„ÙˆØ«Ø§Ø¦Ù‚ Ø§Ù„Ù…ÙƒØªÙˆØ¨Ø©. Ù„ØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ØŒ Ø§Ø³ØªØ®Ø¯Ù…Øª Ø·Ø±ÙŠÙ‚Ø© ØªÙØ§Ø¹Ù„ÙŠØ©. Ù†ØªØ¬ Ø¹Ù† Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø£Ù† Ø§Ù„Ø³Ù„ÙˆÙƒÙŠØ© ÙÙŠ Ø¥Ø¬Ø±Ø§Ø¡ Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ø¬Ø¯Ø¯ ØªÙ…Ø«Ù„Øª ÙÙŠ Ø«Ù„Ø§Ø«Ø© Ø¬ÙˆØ§Ù†Ø¨: 1) Ø§Ù„ØªØÙÙŠØ² Ø§Ù„Ø¥ÙŠØ¬Ø§Ø¨ÙŠ Ù…Ù† Ø§Ù„Ù…Ø¹Ù„Ù…. 2) Ø§Ø³ØªØ¬Ø§Ø¨Ø© Ø¥ÙŠØ¬Ø§Ø¨ÙŠØ© Ù…Ù† Ø§Ù„Ø·Ù„Ø§Ø¨ Ùˆ 3) Ø§Ù„ØªØ¹Ø²ÙŠØ² Ø§Ù„Ø¥ÙŠØ¬Ø§Ø¨ÙŠ Ù…Ù† ÙƒÙ„ Ù…Ù† Ø§Ù„Ù…Ø¹Ù„Ù… ÙˆØ§Ù„Ø·Ø§Ù„Ø¨. Â